Pengaruh Kualitas Produk Promosi dan Harga terhadap Keberhasilan Usaha Kedai Nuna di Desa Pelaga Badung - Ni Luh Rista Pratiwi; Cokorda Istri Agung Vera Nindia Putri; I Made Kartika (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are a driving force behind the food and beverage industry's significant contribution to national economic growth, job creation, and regional economic development. Business success is a crucial indicator of MSME sustainability and is influenced by various factors, including product quality, promotion, and price. Observations and customer interviews at Kedai Nuna in Pelaga Village, Badung, revealed that the business faces challenges such as fluctuating customer traffic, intensifying competition, suboptimal promotional efforts, and a brand image that fails to provide a competitive advantage over rivals. This study aims to analyze the impact of product quality, promotion, and price on the business success of Kedai Nuna in Pelaga Village, Badung. The study employs an associative research design and a quantitative methodology. A sample of 105 respondents was selected using a combination of purposive sampling and probability sampling methods. Data collection involved observation, interviews, questionnaires, and document analysis. Data analysis was conducted using multiple linear regression with SPSS version 25 software, encompassing tests for validity, reliability, classical assumptions, the coefficient of determination, the F-test, and the t-test. The results indicate that product quality, promotion, and price have a positive and significant effect both simultaneously and partially on the business success of Kedai Nuna. These findings suggest that enhancing product quality, implementing effective promotions, and setting appropriate prices can boost competitiveness, attract consumers, maintain customer loyalty, and drive sustainable business success.